Analysis of the elastic and inelastic behaviour of healthy and diseased arterial tissue - Maher, Eoghan (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2012)
Mechanical factors play a key role in determining the success of clinical procedures such as balloon angioplasty and stenting that aim to increase lumen size in atherosclerotic lesions. Finite element modelling is commonly used to model such surgical interventions but the accuracy of these models is limited by the accuracy of the material model used for both the artery and plaque. It is evident that a thorough understanding of the mechanical behaviour of both healthy and diseased arterial tissue is desirable to aid in the treatment of atherosclerosis. In particular, little data is available relating to the inelastic mechanical properties of either arterial tissue or atherosclerotic plaques. The objective of this thesis is to further characterise the mechanical properties of healthy and diseased arterial tissue with a particular focus on stress softening and permanent set following non-physiological levels of loading.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin.